Tax Compliance as an Element of the Corporate Compliance Management System - Sulik-Górecka, Aleksandra (Tax compliance jako element systemu zarządzania zgodnością w przedsiębiorstwie, 2022)
The aim of the paper was to identify areas of the compliance management system and assess the advisability of including tax compliance within the compliance management system. The methodology involved an analysis of relevant literature, legal acts and compliance standards. The empirical part presents the results obtained, having analysed areas of compliance management systems in a sample of ten entities listed on the WSE and included in the WIG20 index. The studied entities were found to present a variety of information on compliance management systems without taking into account the area of tax compliance. According to the author, the implementation of a coherent overall compliance management system would bring many benefits regarding the fulfillment of tax obligations – e.g. in the field of Mandatory Disclosure Rules (MDR) or transfer pricing – and also facilitate the conclusion of the so-called cooperation agreements in the area of taxes and the Advanced Pricing Agreements (APA).
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 1, s. 44-57
Keywords: management; taxes; corporate governance; corporate social responsibility; zarządzanie; podatki; ład korporacyjny; społeczna odpowiedzialność biznesu